Factors affecting FTSE Bursa Malaysia Kuala Lumpur Composite Index (KLCI) stock market / Nurul Shakim Shahdan - Shahdan, Nurul Shakim (Faculty of Business and Management, 2018)
The main purpose of this study is to investigate the relationship between factors that affecting FTSE Bursa Malaysia KLCI stock market in Malaysia. There are three factors that affecting the FTSE Bursa Malaysia KLCI stock market which are Interest Rate (IR), Oil Price (OP) and Money Supply (MS). This research paper employed Multiple Linear Regression method in order to find out the answer the objectives of this study. In addition, the data that has been collected is from year 2010 until 2017 by using quarterly basis and it is about 32 observations of data. From the result, it reveals that interest rate has a positive insignificant relationship towards the FTSE Bursa Malaysia KLCI stock market. While another two variable which is oil price and money supply give positive significant impact towards the FTSE Bursa Malaysia KLCI stock market. For diagnostic checking, there is no problem exist has been detect. Overall, these results give better additional understanding to the factors that affecting FTSE Bursa Malaysia KLCI stock market which is should be advantages and useful to the investors or speculators.